FNAC diagnosis of MultilocularAmeloblastoma of the Mandible: A Case Report - Mitra, Pradeep V; Raju, Kalyani; Murthy, Prashant S (Annals of Pathology and Laboratory Medicine, 2019)
Ameloblastoma is most common benign epithelial odontogenic tumor with malignant potential usually located in jawbone. This tumor is reported to constitute 1-3% of tumors and cyst of jaws. It is common between 3rd to 5th decades of life with equal sex distribution. It often presents as a slow growing painless swelling causing perforation of buccal bone along with infiltration of surrounding soft tissue. It has a very high recurrence rate of over 50% even after wide excision. We present a case of Ameloblastoma in a 71 year female to highlight its cytological features.